1985
DOI: 10.1056/nejm198501243120403
|View full text |Cite
|
Sign up to set email alerts
|

Familial IgA Nephropathy

Abstract: The evaluation of familial glomerulonephritis in patients with IgA nephropathy who were from central and eastern Kentucky resulted in the discovery of potentially related pedigrees containing 14 patients. An additional 17 members of the pedigrees had clinical glomerulonephritis, and 6 had "chronic nephritis" noted on their death certificates. Six patients with IgA nephropathy had a common ancestor. In addition, both parents of six patients with the disease came from families with other cases of IgA nephropathy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(39 citation statements)
references
References 26 publications
2
37
0
Order By: Relevance
“…The proband suffered from renal failure and became dialysis-dependent at the age of 59, 4 years after the onset of chronic nephrotic syndrome [4]. Hereditary renal disorders include autosomal dominant polycystic kidney disease [6], familial IgA nephropathy [7], familial hematuria [8], and Alport’s syndrome [9]. The clinical symptoms and laboratory data showed that our patients had none of the above disorders, indicating that the renal failure in our DRPLA patients is not associated with known familial renal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The proband suffered from renal failure and became dialysis-dependent at the age of 59, 4 years after the onset of chronic nephrotic syndrome [4]. Hereditary renal disorders include autosomal dominant polycystic kidney disease [6], familial IgA nephropathy [7], familial hematuria [8], and Alport’s syndrome [9]. The clinical symptoms and laboratory data showed that our patients had none of the above disorders, indicating that the renal failure in our DRPLA patients is not associated with known familial renal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Immunologic studies in the families of patients have revealed abnormalities of the immune response similar to those found in affected patients. Significant associations between the incidence of IgA nephropathy and some class I (HLA-B12, B35) and II (HLA-DR1, DR4) major histocompatibilities have been reported [22, 23, 24, 25]. Higher frequencies of a homozygous null C4 phenotype [26]and a C3FF phenotype [27]have been described.…”
Section: Epidemiologymentioning
confidence: 99%
“…Familial clustering [22]and geographic variation in the prevalence of the disease are well recognized. Immunologic studies in the families of patients have revealed abnormalities of the immune response similar to those found in affected patients.…”
Section: Epidemiologymentioning
confidence: 99%
“…Subsequently, Julian et al studied a pedigree encompassing seven generations including 14 patients with biopsy-proven IgAN, 17 with clinical hematuria or proteinuria, and six with Bright’s disease on their death certificates [10]; this has been followed by scattered reports of single families [11]. More recently, Schena et al [12]studied 269 relatives from 48 families of IgAN patients and found urinary abnormalities in about 23% of the relatives.…”
Section: Familial Presentationmentioning
confidence: 99%